Test Loan Loss Provisioning Hypotheses for Chinese Banks from 2013 to 2018 - Ziyi, Qian (2019)
This study investigates loan loss provision behavior in Chinese commercial banks through the panel data of 227 banks from 2013 to 2018. According to the previous literature, four hypotheses are proposed, including income smoothing, capital management, business cycle and X-efficiency. Generalized Method of Moments (GMM) is used to test the variables of loan loss provisions and X-efficiency is measured by Stochastic Frontier Approach (SFA). The mean cost efficiency of Chinese banks over the period 2013-2018 near 92.9 percent. The existence of income smoothing, capital management and business cycle behavior in Chinese banking industry have been proved by this study, but fail to find the X-efficiency behaviors.